2021
DOI: 10.1007/s10826-021-01936-0
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Correlates of Picky Eating And Overeating in School-aged Children: A Portuguese Population-based Study

Abstract: All procedures complied with legal requirements by establishing protocols with the different entities involved (Ministry of Education and the Data Protection Authority in Portugal). Schools were contacted, and authorization was provided by the directorial/pedagogical boards of the schools. All parents received a letter explaining the study, main goals and procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(52 reference statements)
1
2
0
1
Order By: Relevance
“…Among the five eating behavior patterns, about 26.4% of adolescents were categorized in the "Picky eating" class, which has a similar prevalence to the one observed in another Portuguese study [22] that found a picky eating frequency of 23.1% in a school-aged sample with, on average, 10.8 years of age. Our finding may suggest that picky eating behavior was relatively frequent in this age group, although picky eating has been reported, in most cases, as a transient behavior, having the highest prevalence around 2 years of age, followed by a decline until 6 years of age [42,43].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Among the five eating behavior patterns, about 26.4% of adolescents were categorized in the "Picky eating" class, which has a similar prevalence to the one observed in another Portuguese study [22] that found a picky eating frequency of 23.1% in a school-aged sample with, on average, 10.8 years of age. Our finding may suggest that picky eating behavior was relatively frequent in this age group, although picky eating has been reported, in most cases, as a transient behavior, having the highest prevalence around 2 years of age, followed by a decline until 6 years of age [42,43].…”
Section: Discussionsupporting
confidence: 79%
“…Children and adolescents whose mothers had a lower age, educational level, and weight tended to have a greater risk of developing picky eating behaviors (rejection of a variety of both familiar and unfamiliar foods) [19,20]. In other studies, those who had siblings showed a lower risk of being characterized as picky eaters [21], and those with lower income were more likely to overeat (of an objectively large amount of food) [22,23].…”
Section: Introductionmentioning
confidence: 90%
“…Picky eating is associated with emotional and behavioural problems, including internalising and externalising problems (32-34). Moreover, a population-based study indicated that internalising and externalising problems predicted picky eating in children from 6 to 18 years old (34). Children's avoidance and restrictive eating pattern might impair their overall psychosocial functioning, resulting in behavioural and emotional problems (35).…”
Section: Discussionmentioning
confidence: 99%
“…1 引言 挑食行为是儿童普遍存在的饮食问题 (Chilman et al, 2023;Wolstenholme et al, 2020), 调查发现在 7~12 岁中国儿童中, 59%的儿童存在不同程度的挑 食行为 (Xue et al, 2015)。挑食行为是指儿童由于拒 绝大量食物而导致摄入的食物种类不足 (Dovey et al, 2008;Taylor & Emmett, 2019), 表现为不愿意吃 某类熟悉的食物或拒绝尝试新的食物 (Taylor et al, 2015)。挑食行为是喂养困难谱系中一种常见的饮 食问题 (McCormick & Markowitz, 2013), 会导致儿 童总体食物摄入量减少 (Pereboom et al, 2023), 饮 食缺乏多样性还会导致营养成分缺失 (Northstone & Emmett, 2013)。长此以往, 挑食行为会发展出饮 食失调等问题 (Machado et al, 2021), 增加肥胖发 生和生长不良的风险 (Demir & Bektas, 2017;Kutbi, 2021)。因此, 儿童挑食行为的研究具有现实意义, 对改善儿童的不良饮食习惯促进儿童健康成长有 重要的参考价值。 儿童挑食行为的影响因素模型指出社会环境 因素和认知因素是调节儿童挑食行为的关键因素 (Lafraire et al, 2016)。在社会环境因素方面, 早期 喂养方式被认为是儿童挑食行为最重要的"塑造 者" (Brown et al, 2022;Harris et al, 2016;Taylor & Emmett, 2019)。已有研究关注父母用食物作为非营 养补充目的的喂养行为, 比如将食物作为奖励来促 进或巩固好的行为和表现 (Lo et al, 2016;Morrison et al, 2013), 这 种 喂 养 方 式 被 称 为 工 具 性 喂 养 (Instrumental Feeding; Mason, 2015;Nembhwani & Winnier, 2020)。研究表明工具性喂养是非反应性喂 养方式的一种, 它干扰了儿童正确识别饥饿信号和 调节食欲的能力 (Byrne et al, 2017;Harris et al, 是奖赏环路的关键节点 (Li, Hu et al, 2023), 参与 调控对食物的"喜欢"和"想要", 决定了对食物的趋 近或远离 (Campos et al, 2022;Jiang et al, 2015; Morales & Berridge, 2020)。以往研究发现尾状核、 壳核和伏隔核负责编码食物的主观奖赏价值, 参与 形成对食物的主观偏好 (Hommer et al, 2013;Luo & Han, 2023;Terenzi et al, 2022;van den Bosch et al, 2014), 而且在厌恶动机驱动的行为中也发挥作用 (Royet et al, 2016), 这与挑食行为的内涵相似。此 外, 尾状核也参与感觉信息加工 (Yuan et al, 2022), 有研究表明楔前叶和尾状核是感觉加工敏感性的 神经基础 (Acevedo et al, 2018(Acevedo et a...…”
unclassified